Evaluation of Anti-Cancer Activity of Silver@Gold Nanoparticles by Hybrid Technique - Zainab Shaheed Kadhim; Hammod, Haider Y. (Iraqi Journal of Laser, 2024)
This research deals with the evaluation of the anti-cancer activity of Ag@Au NPs synthesis by a hybrid system combining laser and plasma jet techniques. The effect of NPs on inhibiting the growth of breast cancer cells and normal cell lines was studied. Firstly, silver nanoparticles were prepared using a Nd:YAG laser with a wavelength of 1064 nm, a frequency of 6 Hz, an energy of 1000 mJ, and a number of pulses of 558. In the second step, we take different ratios between Ag NPs and gold salts as follows: (1:9, 2:8, and 3:7), respectively, and exposed to a plasma jet system for 3 minutes. The NPs were checked using X-ray diffraction, UV-vis spectroscopy, and field emission scanning electron microscopy (FE-SEM). The highest rate of inhibition of breast cancer cells was 66% after 48 hours when the concentration was 100% with a ratio of 3:7. As for its toxicity to normal cells, the highest toxicity was 16% after 24 hours when the concentration was 100% for 3:7. The expected results could provide new light on the effectiveness of these particles in treating cancer and stimulate future research in this field.